Morphological classification of NADPHd-positive and -negative myenteric neurons in the porcine small intestine - Brehmer, Axel; Stach, Werner (Cell and Tissue Research, 1997)
In this study, the neuronal nitric oxide synthase (nNOS)-related NADPHd reaction was combined with a silver impregnation method to visualize the morphology of nitrergic and non-nitrergic enteric neurons in the pig. Based on colour combination, NADPHd-positive and impregnated, NADPHd-negative but impregnated and NADPHd-positive but non-impregnated groups of nerve cells could be distinguished in whole-mounts of the small intestine. Neurons of the first two groups could be classified morphologically. NADPHd-positive and impregnated cells showed type III and type VI morphology, the first being located preferably in the upper, the latter in the lower small intestine. Both project largely in an aboral direction. NADPHd-negative but silver impregnated are the orally projecting type I, the adendritic, mostly circumferentially projecting type II, the vertically - to the submucous plexuses - projecting type IV and the aborally projecting type V neurons. Given that NADP-PHd and nNOS are identical, we conclude that type III and type VI neurons are nitrergic and type I, II, IV and V neurons are non-nitrergic. A considerable number of mostly smaller NADPHd-positive but non-impregnated neurons could not be classified.
Keywords: Axonal projection; Enteric nervous system; NADPH diaphorase; Neuron type; Nitric oxide synthase; Pig; Silver impregnation